Pengaruh Prestasi Dan Efikasi Diri Terhadap Minat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Muhammadiyah Bengkulu - Meirani Meirani; Leoni Puji Lestari (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine whether there is an effect of achievement on the entrepreneurial interest of students of Economics Education FKIP University of Muhammadiyah Bengkulu. Knowing whether there is an effect of self-efficacy on the entrepreneurial interest of Economic Education FKIP students, University of Muhammadiyah Bengkulu. Knowing the effect of achievement and self-efficacy on entrepreneurial interest in Economics Education FKIP University of Muhammadiyah Bengkulu. This type of research is quantitative research. The population of this study were students of economic education at Muhammadiyah Bengkulu University class 2018, 2019, 2020 who were still active. The sample used is saturated sampling. Data collection techniques using observation, questionnaires, and documentation. The data analysis technique used multiple linear regression. Achievement has an effect on entrepreneurial interest in Economics Education students, FKIP University of Muhammadiyah Bengkulu, obtained from the value of t-count < t-table which is 3.535 < 1.660 so that Ha1 is accepted and Ho1 is rejected. Self-efficacy has an effect on entrepreneurial interest in Economics Education students, FKIP Muhammadiyah Bengkulu University, obtained from the value of t-count < t-table which is 3.508 < 1.659 so that Ha2 is accepted and Ho2 is rejected. Achievement and Self-Efficacy on Entrepreneurial Interest in Economic Education FKIP students, University of Muhammadiyah Bengkulu, has a positive and significant effect on entrepreneurial interest in Economics Education FKIP students, University of Muhammadiyah Bengkulu. This is obtained from the results of the calculated f value > f table 7.364> 3.08. So that Ha3 is accepted and Ho3 is rejected and the level of influence is 12.5%.